Biofaktor MTA (Imicryl) Sebagai Alternatif Bahan Pulp Capping Bioaktif Dalam Perawatan Gigi Permanen: Laporan Kasus - Fitriyani, Rheina; Nurdin, Denny (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2025)
Vital pulp therapy is a conservative dental treatment aimed at maintaining the vitality of the tooth by stimulating pulp tissue healing, promoting dentinal bridge formation, and preventing pulp necrosis. Pulp capping is one of the vital pulp therapy procedures that can be performed on permanent teeth. The success of pulp capping treatment depends on proper caries excavation and the selection of an optimal capping material. Biofactor MTA (Imicryl) is a next-generation calcium silicate–based bioactive pulp capping material developed to overcome the limitations of conventional pulp capping agents. This case report discusses the treatment of a permanent tooth diagnosed with reversible pulpitis on tooth #47, with a treatment plan of pulp capping using Biofactor MTA (Imicryl). The treatment procedure included caries excavation, application of the Biofactor MTA (Imicryl) material, placement of a glass ionomer base, and Class I composite resin restoration. Evaluation at the sixth week showed the absence of pain symptoms, good pulp vitality, and the formation of reparative dentin. Biofactor MTA demonstrated favorable clinical outcomes and shows potential as an effective, easily applicable, and more economical bioactive pulp capping material among its class for the treatment of vital permanent teeth.  Keywords : Biofactor MTA; pulp capping; bioactive; vital pulp therapy